The Effect of Ankle Weight Training on The Speed of Mawashi Geri Kicking Dojo Ikhlas Pekanbaru - Irma, Riska; Vai, Aref; Fernandes, Oca (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to analyze the effect of Continuous Running training on cardiovascular endurance in badminton extracurricular athletes at SMP Negeri 48 Pekanbaru. The research method used is an experiment with a pre-test and post-test design. Cardiovascular endurance measurements were carried out using the Multistage Fitness Test (MFT) before and after being given Continuous Running training treatment for several weeks. The results showed that there was a significant increase in cardiovascular endurance after being given the training, which was indicated by an increase in the participants' VO2max values. The statistical tests conducted proved that Continuous Running training had a positive effect on increasing aerobic capacity, so it can be recommended as an effective training method for athletes to increase cardiovascular endurance. Based on the research results, it can be concluded that the results of the pre-test with the post-test were analyzed using the t-test, the t-results on the sample using ankle weight load were Tcount 3.571> Ttable 1.943 then H1 was accepted, at level (a) 0.05. This means that there is an effect of ankle weight training on increasing the speed of the Dojo Ikhlas Pekanbaru athlete's mawashi geri kick.